ANALISIS KUALITAS GAS BUANG PADA STEAM BOILER BERBAHAN BAKAR BIO-SOLAR DAN BATU BARA - Ar Rasyid, Moh. Rizal; Anis, Samsudin; Susanto, Susanto; Danang, Setio Wardana (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
Steam boilers fueled by biodiesel and coal are one of the industrial activities that still produce exhaust emissions such as Total Particulate (PM), Sulfur Dioxide (SO2), Opacity, Nitrogen Oxide (NOx), and Carbon Monoxide (CO) which is very dangerous for public health and the environment. Therefore, analysis of flue gas emissions in steam boiler installations equipped with filtration devices (cyclones, water scrubbers, and electrostatic precipitators) before being discharged into the environment is of important. Exhaust gas emission was measured by using a gas analyzer, smoke tester, and portable quality air monitor. The results of exhaust gas emission analysis showed that the average concentration of PM, SO2, and CO did not meet the specified emission quality standard thresholds, exempted for opacity concentration for both steam boilers fueled with biodiesel and coal. It is suspected that this is caused by the sub optimal performance of the filtration equipment used in this system. Therefore, regular maintenance is required, and if necessary, a redesign of the entire system can be carried out.